2010
DOI: 10.1021/ma901842q
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Collapse of Single-Monomer-Thick Monolayers of Poly(n-butyl acrylate) at the Air−Water Interface

Abstract: The behavior of poly(n-butyl acrylate) (PnBA) spread at the air-water interface has been studied for a full range of surface coverages and several molecular weights. At low and intermediate surface coverages, the surface pressure-area isotherm behavior of the polymer is found to follow the expected scaling laws. In the dilute regime the pressure is an increasing function of surface coverage and a decreasing function of molecular weight. In the semidilute regime the surface pressure becomes independent of molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(72 citation statements)
references
References 35 publications
5
67
0
Order By: Relevance
“…Figure 1(A) displays the results from these measurements in plots of monolayer surface pressure (Π) vs. area per hydrophobic (i.e., PnBA) monomer (α). As discussed in detail in our previous publication, 56 the sharp plateau transition in the isotherm of the PnBA homopolymer (black curve) at an area per PnBA monomer of α o ≈ 21.6 Å 2 is due to the formation of a flat (i.e., laterally uniform) single-monomer-thick continuous film of PnBA that is free of voids at that polymer surface concentration. Our previous studies have also demonstrated that, thanks to this property of PnBA, at areas per PnBA monomer less than α o , the monolayer domain formed at the air-water interface by PnBA can be used as end-grafting sites for PEO or PDMAEMA chains for preparation of model non-adsorbing PEO 58, 66 or PDMAEMA 57, 62 brush systems.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Figure 1(A) displays the results from these measurements in plots of monolayer surface pressure (Π) vs. area per hydrophobic (i.e., PnBA) monomer (α). As discussed in detail in our previous publication, 56 the sharp plateau transition in the isotherm of the PnBA homopolymer (black curve) at an area per PnBA monomer of α o ≈ 21.6 Å 2 is due to the formation of a flat (i.e., laterally uniform) single-monomer-thick continuous film of PnBA that is free of voids at that polymer surface concentration. Our previous studies have also demonstrated that, thanks to this property of PnBA, at areas per PnBA monomer less than α o , the monolayer domain formed at the air-water interface by PnBA can be used as end-grafting sites for PEO or PDMAEMA chains for preparation of model non-adsorbing PEO 58, 66 or PDMAEMA 57, 62 brush systems.…”
Section: Resultsmentioning
confidence: 70%
“…Specifically, a laterally-mobile mixed PEO and PDMAEMA brush was prepared by spreading a mixture of two diblock copolymers, poly(ethylene oxide)-poly( n -butyl acrylate) (PEO-PnBA) and poly(2-(dimethylamino)ethyl methacrylate)-poly( n -butyl acrylate) (PDMAEMA-PnBA), onto the air-water interface. Here, PnBA was used as the common hydrophobic block for these copolymers, because the PnBA polymer forms a flat, single monomer-thick, continuous film (free of bare areas) at the air-water interface, 56 and also the grafted PEO and PDMAEMA chains do not have any tendency to adsorb to the surface of the anchoring domain formed by PnBA, 57, 58 which makes the PEO-PnBA and PDMAEMA-PnBA block copolymers uniquely suited for preparation of model non-adsorbing PEO/PDMAEMA brush systems. A laterally-mobile mixed PEO and PDMAEMA brush was prepared from a mixture of PEO 113 -PnBA 100 and PDMAEMA 118 -PnBA 100 diblock copolymers, where the subscripts refer to the number-average degrees of polymerization of the individual blocks; note that, as will be analyzed, in this case the heights of the PEO and PDMAEMA brushes are estimated to be (slightly) mismatched (that is, they differ by a factor less than about two).…”
Section: Introductionmentioning
confidence: 99%
“…21 The relevant findings of the study can be summarized as follows. As demonstrated in Figure 1A, a typical surface pressure (Π) vs area per chain (α) isotherm of a PnBA polymer exhibits a sharp transition upon compression from a compressible fluid state to a plateau of surface pressure (for instance, in the case demonstrated in the figure (DP n = 102), the transition occurs at an area per chain value of α o = 2120 Å 2 /chain).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the previous section, in a monolayer formed by a PnBA homopolymer, this monolayer collapse leads to formation of micrometer-scale aggregates ("domains"). 21 To test whether the same happens in the PEO−PnBA monolayer, the lateral uniformity of the monolayer film was examined at an area per chain condition of α = 2000 Å 2 /chain by atomic force microscopy (AFM). The resultant image is presented in Figure S1 of the Supporting Information (SI).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, during monolayer compression, this chain collapsed regime starts at the surface polymer concentration corresponding to the full surface coverage condition. 4 In 1946, Crisp reported extensive data comparing surface pressure-area isotherm data for a wide range of different polymers;…”
mentioning
confidence: 99%